Hydroethanolic extract of Schinus terebinthifolia as a promising source of anti-influenza agents: Phytochemical profiling, cheminformatics, molecular docking and dynamics simulations - Napapuch Nopkuesuk; Anuwatchakij Klamrak; Jaran Nabnueangsap; Jaraspim Narkpuk; Shaikh Shahinur Rahman; Yutthakan Saengkun; Piyapon Janpan; Thananya Soonkum; Poramet Sitthiwong; Nisachon Jangpromma; Sirinan Kulchat; Kiattawee Choowongkomon; et al. (PLoS ONE, 2025)
Although Schinus terebinthifolia (commonly known as Brazilian peppertree) has been documented to possess various biological activities, such as anticancer, antibacterial, and antioxidant properties, its anti-influenza activity has not yet been documented. Here, an aqueous-ethanolic extract (30% v/v ethanol solution), prepared from its aerial parts (leaves and stalks), was established to determine whether it is a rich source of antiviral agents. The hydroethanolic plant extract, with a TPC value of 264.11 mg (GAE)/g DE, exhibits a promising IC50 value of 16.33 μg/mL, similar to that of authentic quercetin (IC50 = 12.72 μg/mL), and approximately 5.34 times higher than that of gallic acid (IC50 = 3.06 μg/mL) as determined by the DPPH assay. This extract contains 1.71 mg of gallic acid (representative marker) per gram of dried plant material, according to HPLC analysis. Using untargeted metabolomics analysis coupled with a series of cheminformatics tools (MetFrag, SIRIUS, CSI:FingerID, and CANOPUS), we ultimately proved that the S. terebinthifolia hydroethanolic extract contains simple phenolics (e.g., methyl gallate, ethyl gallate, and chlorogenic acid), flavonoids (afzelin and myricitrin), dicarboxylic acids, and germacrone. As anticipated, the plant extract exhibited anti-influenza activity with an IC50 of 2.21 μg/mL (CC50 > 50 μg/mL) and did not exert hemolytic activity at the concentration of 2000 μg/mL, underscoring its efficacy as a safe antiviral solution. In silico molecular docking and dynamic simulations suggest that neuraminidase and the cap-binding domain of influenza RNA polymerase (PB2) are preferentially targeted for inhibition by the detected metabolites. Owing to the diverse therapeutic effects of secondary metabolites, the anti-H5N1 activity of the newly developed plant extract is currently under investigation.